Creativity for sustainability: An integrative literature review - Saleh, Rabab; Brem, Alexander (Journal of Cleaner Production, 2023)
How can creativity foster sustainability? This is a recently emerging question that sees current approaches to sustainability solutions as lacking the use of creativity. Creativity is thus seen as an aspiration to re-create and discover new paths to accelerate the transitions towards sustainability. We apply an integrative review of the creativity for sustainability literature with an in-depth analysis of 86 journal articles. In addition, we draw on insights from innovation and business studies and from the social sciences on sustainability transitions. The findings indicate four levels of creativity for sustainability including the individual, community, organizational, and institutional levels. On each of these levels, a set of indicators has been identified.
CRIS-Team Scopus Importer:2023-01-20
Keywords: Creativity; Green; Innovation; Sustainability; Sustainability transition; Kulturelle Vielfalt